To test or preserve? The prohibition of Gen 2.16-17 in the thought of two second-century exegetes - Steenberg, Matthew C. (Gregorianum, 2005)
«Why forbid the tree?» Of all the questions that arise from a reading of the Genesis protology, that over why God forbade Adam and Eve the fruit of the tree of knowledge is of perennial curiosity. The present article examines the exegesis of two second-century sources, Theophilus of Antioch and Irenaeus of Lyons, each of whom considered the question of profound importance in anthropological and soteriological reflections. An emphasis on the prohibition as a test in Theophilus meets the alternate interpretation of the prohibition as a formative construct in defining the limits of human intellectual capability according to Irenaeus. These are explored in detail, and at the article's end are synthesised in a reading of the Genesis prohibition that makes use of both points of emphasis. «Perché vietare l'albero?». Di tutte le questioni che sorgono dalla lettura della protologia della Genesi quella riguardante il perché Dio vieti ad Adamo ed Eva il frutto dell'albero della conoscenza suscita da sempre curiosità. Il presente articolo esamina due fonti del II secolo, Teofilo d'Antiochia e Ireneo di Lione, ciascuno dei quali considerò la questione d'estrema importanza riflettendovi dal punto di vista antropologico e soteriologico. Un'enfasi sulla proibizione come prova in Teofilo incontra l'interpretazione alternativa della proibizione come concetto formativo nel definire i limiti della capacità intellettiva umana secondo Ireneo. Queste posizioni sono esaminate dettagliatamente e sintetizzate, infine, in una lettura della proibizione della Genesi che tenga conto dell'enfasi di entrambi i punti di vista.